IMPROVING RADIATION DIAGNOSTICS OF DENTAL DISEASES - Hamdamova Lola Zarifovna (Ustozlar uchun, 2025)
Diseases of the maxillofacial region of the skull and teeth occupy a special place in the clinic due to their significant prevalence, difficulties in diagnosis and treatment, and extremely diverse and complex symptoms (Borovsky E.V., 2004; Ternovoy S.K., et al., 2004; Alpiste-illueca F., 2004; Rabukhina H.A., et al., 2006).